The catholic thought in the context of political clashes of 1930s in Brazil - Souza, Aline Christine de; Derisso, José Luis (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
The production of this article results from studies realized in the scope of a research of scientific initiation which the object is the Catholic Thought in Brazil in the context of the clashes with the so-called “Pioneers of New Education” that preceded the elaboration of the Constitution of 1934. It is a bibliographic research that prioritized the study, on the one hand, of the fundamentals of Catholic Thought in ecclesiastic documents and, on the other hand, of its manifestation in Brazil through “A Ordem” magazine, its mainly public expression. It is concluded that the Catholic Thought constitute an important ideological ingredient in the context in question and develops in accord with the class struggle in Europe and the fractions of the dominant class in Brazil, expressing the resistance of the Catholic Church to the republican model of school and to the ideal, also republican, of State secularism.